Clinical Features and Efficacy of Lens Surgery in Patients with Lens Subluxation Misdiagnosed as Primary Angle-Closure Glaucoma. (3rd April 2019) - Zhang, Yinglei; Zong, Yuan; Jiang, Yongxiang; Jiang, Chunhui; Lu, Yi; Zhu, Xiangjia
ABSTRACT: Purpose : To investigate the clinical features and efficacy of lens surgery in patients with lens subluxation misdiagnosed as primary angle-closure glaucoma. Methods : In total, 2054 inpatients with primary angle-closure glaucoma were consecutively recruited. Eighty-five of the patients were rediagnosed as lens subluxation following ultrasound biomicroscopy after hospitalization. Lens surgeries were performed in all patients, and 35 had a follow-up of at least 12 months. Risk factors of postoperative intraocular pressure control were identified with multivariate logistic regression analysis. Results : Eighty-five inpatients (4.1%, 85/2054) with lens subluxation were misdiagnosed as primary angle-closure glaucoma, of which 71.8% (2.97% of all cases, 61 out of 2054 subjects) had ocular blunt trauma and 18.8% (0.78% of all cases, 16 out of 2054 subjects) had spontaneous dislocation. Lens surgery significantly decreased the intraocular pressure and improved best-corrected visual acuity, meanwhile increased the anterior chamber depth (all P < 0.001). Postoperatively, the intraocular pressure was controlled with antiglaucomatous eye drops administration in 17 eyes, in which greater range of preoperative angle closure and zonular dialysis, and longer operation time delay were detected. Risk factors for poor postoperative IOP control were more quadrants of angle closure ( P = 0.038) and operation time delay ( P = 0.045). Conclusion : Lens subluxation was the major cause of the misdiagnosed cases as primary angle-closure glaucoma. Misdiagnosed patients could benefit from the lens surgery, while more angle-closure quadrants and operation time delay indicated worse postoperative intraocular pressure control.